CONCEPTION OF ETHICS, MORALS, AND SCIENCE IN THE PERSPECTIVE OF HUMANISM - Tamaro Ulzima Stari; Nofa Nadhifus Sakinah; Sofa Sofiana; Tulchaimah, Ani gusmiarni (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Science plays an important role in the development of human civilization. However, the advancement of science cannot be separated from the ethical aspect, especially in the context of sustainability and humanity. This article discusses the ethics of science from a religious perspective, focusing on how religious values ​​can be a moral guideline in the development and application of science. Through a qualitative approach and literature study from various religious sources such as Islam, Christianity, and Hinduism, it was found that each religion emphasizes moral responsibility, justice, and the usefulness of science for life. Thus, the integration of scientific ethics and spiritual values ​​is important to ensure that science is used for the good of humanity and the environment. Keywords: ethics, science, religion, morality, responsibility.